Is eating organic a healthy or safer option? Health claims for organic food consumption, food quality and safety – A systematic review - Ghai, Sneha; Sharma, Ashok; Dasgupta, Pinaki (Indian Journal of Community Health, 2017)
Universally, there has been an increased awareness about the harmful effects of chemical inputs used for production of food on soil composition, environment and human health. This has triggered the consumption level of organic food products. India has witnessed a tremendous growth in domestic as well as export market. The demand is mainly driven by consumer perceptions that organic farming is more sustainable, produces healthy food, pesticide-free and safeguards the environment & biodiversity. Organic food producers also manifests the quality and safety of food. These claims which are perceived and professed as beneficial can only be accepted if they are tested and validated. Therefore, the foremost objective of this review paper is to provide an update on set of studies related to scientific evidence for nutritional composition marking the quality of organic foods vis-à-vis conventional foods and its impact on human health. Secondly, the paper examines the comparison of the sensory quality of the organic food, and thirdly the food safety aspect of organically as compared with conventionally grown foods. Past few controlled studies have proved that there is no such evidence of differences in concentration of various nutrients amongst organic and conventional foods. Furthermore, there are certain issues related to the impact and assessment of these nutrients in organic food which requires some future directives. Owing to the heterogeneity in results observed related to nutritional quality and safety of organic foods, technological aspects together with sensory parameters are the best for future comparative studies. To safeguard the public health and to avoid the difference in sampling and sample results, testing laboratories should also be adhering to uniform standards. Organic food business in India lack standard guidelines for quality, policy framework for domestic and export market. Also, traceability is another factor which should be given prime importance to ensure removal of fraudulent practices.